2021
DOI: 10.3390/w13172441
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Modification of the Structure of Water and Water-Containing Systems in Changing Their Biological, Therapeutic, and Other Properties Overview

Abstract: Based on published research on modifying the structure of water and water-containing systems, we assess external influence methods: temperature, magnetic field, light radiation, and their combination. We evaluate changes in the electrophysical, photo- and pH-metric biological, therapeutic, and other properties of water systems using non-destructive electrophysical research methods, i.e., thermometry, pH, laser interference, dynamic light scattering, microelectrophoresis, conductivity, surface tension, dielectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Structured water has antioxidant properties due to the quasi-free, delocalized electrons that circle around the hexagonal rings of water. The delocalized electrons can readily quench excess generation of free radicals produced along the electron transfer chain during photosynthesis in heat and/or water stressed plants [20][21][22][23]25]. Antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidases (GPxs are widely recognized in quenching reactive oxygen species (ROS) that are generated in the electron transfer chain in photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structured water has antioxidant properties due to the quasi-free, delocalized electrons that circle around the hexagonal rings of water. The delocalized electrons can readily quench excess generation of free radicals produced along the electron transfer chain during photosynthesis in heat and/or water stressed plants [20][21][22][23]25]. Antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidases (GPxs are widely recognized in quenching reactive oxygen species (ROS) that are generated in the electron transfer chain in photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical properties of irrigation water can be manipulated by several energy-based treatments [13]. Decades of research have shown that bulk water exposed to energy sources that strengthen or shorten the hydrogen bonds in water molecules such as infrared radiation, magnetic fields, sonic waves, mechanical vibrations, or low temperatures will add structure to water [14][15][16][17][18][19][20]. As water is exposed to low temperatures, or a range of energy sources, the hydrogen bonds become shorter, and the bond angles widen from 104º to 109.5º.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors, such as magnetic field, solution composition, temperature, and others, can affect the structure of water and alter the sizes of water clusters [3,15,[17][18][19][20]. The structure of aqueous solutions also changes in the near-wall layer, depending on the material of the surface and the substance dissolved in the water [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Water and water-containing systems can undergo structural modifications due to various low-energy effects [2,3,15,[18][19][20][23][24][25][26]. These structural changes can alter water's biological, therapeutic, and other properties and applications [17]. Experimental and clinical evidence supports that water's structure influences biological activity and other characteristics.…”
Section: Introductionmentioning
confidence: 99%